Faculty Experience with Motivating and Inhibiting Factors on Online Teaching : the Case of Two Universities in Baku - Suleymanli, Rabiya (ADA University, 2021)
The primary purpose of this research is to investigate the motivating and inhibiting factors that affect faculty's online teaching experience at two Baku Universities. During the special quarantine regime caused by COVID 19, all higher educational institutions in Azerbaijan transferred to online teaching. The analysis of the prior research works showed a lack of research on faculty motivation for online education and a lack of methodological approaches to measuring faculty’s motivation levels. This research's main target is to identify motivating factors for faculty in online teaching. It also explored barriers to online teaching in order to understand inhibiting factors for faculty. The research work covers two Universities in Baku- University A, and University B. During the research, semi-structured interviews and document analysis were used as qualitative research methods to explore faculty's experience regarding online teaching. Moreover, semi-structured interviews were conducted with a dean and program director to understand the university management's role in faculty motivation. Twelve faculty members from different departments, one program director, and one dean participated in the interview process. Based on the interviews, the study explores motivating (extrinsic and intrinsic) and inhibiting (extrinsic and intrinsic) factors for faculty in their online teaching experience. Main motivational factors for instructors are: overall job satisfaction, administrative and technical support, students’ active participation, technological advantages, trainings. Major demotivating (inhibiting) factors for university instructors are: lack of IT skills, cheating in exams, dissatisfaction with the change of form of contact, malfunction of platforms, weak internet connection. One major result of the research is that the role of administration is important for university instructors. At the end of the study, some limitations and recommendations for further research are pointed out. Research findings can be helpful for further research on online teaching in the Azerbaijani context.
Keywords: Education; Online teaching.; Online teaching -- Azerbaijan.; Distant education.; Distant education -- Azerbaijan.; Education -- Azerbaijan.